GWO tuned multi degree of freedom PID controller for load frequency control - Charan Patel, Nimai; Kumar Debnath, Manoj; Prasad Bagarty, Durgesh; Das, Pranati (International Journal of Engineering and Technology, 2018)
In order to enhance the control action, in this article multi degree of freedom PID controllers (MDFPID) like 2DOF-PID and 3DOF-PID controllers are suggested for frequency control in a multi-unit hydro-thermal interconnected system. The finest gains of the recommended MDFPID controllers are achieved with Grey Wolf Optimization (GWO) Technique considering a time based evaluative function. The dom-inating performance of the suggested control technique is validated by relating the outcomes with a pre-published journal results. The robust behavior of the MDFPID controller is also validated by abruptly amplifying the loading of the system. The system dynamic responses are analyzed in consideration with time response parameters like minimum undershoots, settling time and peak overshoots.Â Â